VIKOR Method for Evaluating the Management Quality of Teacher Education with Probabilistic Hesitant Fuzzy Information - Li Zhiqi (Discrete Dynamics in Nature and Society)
In the era of enhancing the quality of education, teacher quality, as the core factor affecting the quality of education, has received unprecedented attention in the field of education. The monitoring on teacher quality is the basis of fully understanding and effectively improving the quality of teachers in compulsory education within the county. Comprehensive and systematic study on teacher quality control in compulsory education within the county is the key to improve the teacher quality of it as well as improve and complement research in related fields. And in stark contrast to the importance of the problem, there is no in-depth and systematic result on the monitoring on teacher quality within the county which becomes a matter of concern in current research in the field of education issues. And the management quality evaluation of teacher education is frequently viewed as the multiple attribute decision-making (MADM) issue. An extended VIKOR model is established to provide a new approach to solve the management quality evaluation of teacher education. The VIKOR method with probabilistic hesitant fuzzy information is applied to rank the optional solutions. Lastly, a numerical example about management quality evaluation of teacher education is illustrated to test the newly proposed method’s practicability.